The pastoral elegy rocks Shelley’s revisions of an ancient genre open the way to honour Brian Jones - van der Leest, Janneke (Scenari, 2021)
In this article the attention is focused firstly on the ancient genre of pastoral elegy and Percy Bysshe Shelley’s romantic revisions in his ode to John Keats. What do these revisions mean? Secondly, the article will concentrate on two twentieth century elegies. Jim Morrison and Pete Townshend each wrote a poem in remembrance of Rolling Stone Brian Jones, respectively Ode to LA while thinking of Brian Jones, Deceased and the obituary A Normal Day for Brian, the Man who Died Every Day. Do those twentieth century examples follow the ancient genre and its romantic changes? And if so, how? Further, with their poems the writers place themselves as mourners in a specific relation to the deceased who is pictures as a colleague, an example, or a friend. Sometimes the images of the mourned and the mourner intertwine. The pastoral elegy is a matter of representation of the deceased as well as representation of the ones left. And the romantic image of the (misunderstood) genius continues to plays a major role in the game of representation to this day.